The male reproductive accessory glands of the blister beetle Meloe proscarabaeus Linnaeus, 1758 (Coleoptera: Meloidae): Anatomy and ultrastructure of the cantharidin-storing organs - Muzzi, Maurizio (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2020)
Blister beetles owe their name to their ability to release cantharidin, a blistering terpene, the highest concentration of which is retained in male accessory glands. The anatomy and ultrastructure of the three pairs of male reproductive accessory glands and the glandular region of the two vasa deferentia of Meloe proscarabaeus were investigated using light, electron and ion beam microscopy. All of the mesodermal glands here analysed share a common structural organization with an outer muscular layer and an inner glandular epithelium facing a broad lumen in which the secretory products are released. Developed rough endoplasmic reticulum, Golgi systems, abundant mitochondria, numerous secretory vesicles and a microvillated apical membrane are commonly found in the cells of different glandular epithelia, suggesting that all accessory gland pairs as well as the vasa deferentia are involved in an active synthesis. Nevertheless, each pair of glands appears specialized in the production of a specific set of substances, as suggested by the peculiarities in cellular ultrastructure and by the different aspect of the secretions stored in their glandular lumen. The above cited features of male accessory glands of M. proscarabaeus are compared with those of other beetles and some hints on their potential role in producing and/or concentrating cantharidin are provided.